Conformation traits and their genetic and phenotypic associations with health status in young Swedish warmblood riding horses - Jönsson, Lina; Näsholm, Anna; Roepstorff, Lars; Egenvall, Agneta; Dalin, Göran; Philipsson, Jan (Livestock science, 2014)
Health in horses is thought to be influenced by conformation traits, including limb deviations. As few studies on the subject are available, the relevance of selecting for specific conformation traits to improve health is uncertain. The objective was to determine the genetic variation in conformation and relationships between conformation and health status in young riding horses. Analyses included 8187 young horses independently examined for conformation and health, during the Swedish Riding Horse Quality Test (RHQT) for 4–5 year-old horses. Both descriptive conformation traits and assessment scores of conformation were studied. Phenotypic effects were estimated using single trait General Linear Models and heritabilities and genetic correlations using multi-trait linear animal models. Four major health indicators were constructed from the detailed veterinary examinations. Conformation assessment scores were all favourably related to at least one of 4 studied health traits, both phenotypically and genetically. Genetic correlations reached 0.75 between conformation scores for head-neck-body and locomotion examinations, including flexion tests, and 0.43 for limb scores and locomotion examinations. Best health status was found for an intermediate-sized horse, with a well-positioned neck, a light front, and no major limb deviations. This finding was consistent with the role of correct movements at trot. Among limb deviations stiff pasterns, toed-out or toed-in forelimbs, and small or large hock angles showed highest negative effects on health. However, the prevalence of limb deviations was generally low, thus only toed-in forelimbs and small joints had significant genetic correlations to impaired health. Heritabilities for withers height, cannon bone circumference and overall conformation scores (except for limbs), were medium to high (0.20–0.67, s.e. 0.03–0.04). For specific limb deviations, heritabilities were in the range of 0.01–0.15 (s.e. 0.01–0.02) on the observed scale, corresponding to 0.04–0.48 on the underlying quantitative scale. Heritabilities of conformation traits and favourable correlations to health indicate good opportunities for genetic improvement of conformation, and indirectly to some extent also of health. However, only limited improvements could be expected for the prevalence of some limb deviations, where frequencies are already low.